Предмет: Алгебра,
автор: pashabukin01p
Решите уравнение х+2
Ответы
Автор ответа:
0
(2x + 1)*(4x^2-2x+1) / (3*(2x+1)) = (4x^2-2x+1) / 3, x не равно -0,5
(4x^2-2x+1) / 3 + 11/12 = (x+5) / 4, домножаем все так, чтобы общий знаменатель был 12
16x^2 - 8x + 4 + 11 = 3x + 15
16x^2 - 11x = 0
x1 = 0
x2 = 11/16
(4x^2-2x+1) / 3 + 11/12 = (x+5) / 4, домножаем все так, чтобы общий знаменатель был 12
16x^2 - 8x + 4 + 11 = 3x + 15
16x^2 - 11x = 0
x1 = 0
x2 = 11/16
Похожие вопросы
Предмет: Химия,
автор: ermekovaslan88
Предмет: История,
автор: kozaknatali2018
Предмет: ОБЖ,
автор: arslanovnufar
Предмет: Математика,
автор: fardi99
Предмет: Химия,
автор: Аноним